Distribution of the lower boundary functional of the step process of semi-Markov random walk with delaying screen at zero - Nasirova, T. I.; Omarova, K. K. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
On the basis of a given sequence of independent identically distributed pairs of random variables, we construct the step process of semi-Markov random walk that is later delayed by a screen at zero. For this process, we obtain the Laplace transform of the distribution of the time of the first hit of the level zero.